Surgical treatment of a newborn with critical aortic coarctation using palliative stenting: a case report - A. A. Lyapin; P. A. Shushpannikov; I. K. Khalivopulo; R. S. Tarasov (Российский кардиологический журнал)
Introduction. Coarctation of the aorta (CoA) is a congenital severe narrowing of the aortic isthmus, which in turn is often accompanied by impaired organ perfusion or even cardiogenic shock. In newborns with critical CoA in the case of patent ductus arteriosus (PDA) closure, the clinical condition of patients with this congenital heart defect (CHD) sharply worsens and leads to multiple organ failure. In this group of children, mortality ranges from 30 to 50% of infant mortality from CHD. This case demonstrates the positive effect of palliative stenting of a narrowed section of the aorta, which made it possible to safely perform radical surgery for CHD.Case description. Nine-year-old male patient with body weight of 3,5 kg and body length of 53 cm was admitted to the clinic with a diagnosis of CHD: Critical CoA. Secundum atrial septal defect. PDA. Multiple organ failure. Taking into account the severe comorbidity status in the form of multiple organ failure, the high risk of necrotizing enterocolitis, case conference decided to perform a step-by-step CHD treatment as follows: palliative endovascular stenting of critical CoA, followed by radical surgery after stabilization of the patient's condition. The plan was successfully implemented.Conclusion. Сritical CoA stenting can be used as a bridge to radical surgery of the defect in newborns with multiple organ failure. This palliative intervention helps to stabilize the child for up to 3 weeks and more safely perform radical surgery of CoA.